2007
DOI: 10.1007/s00401-007-0243-4
|View full text |Cite
|
Sign up to set email alerts
|

The 2007 WHO Classification of Tumours of the Central Nervous System

Abstract: The fourth edition of the World Health Organization (WHO) classiWcation of tumours of the central nervous system, published in 2007, lists several new entities, including angiocentric glioma, papillary glioneuronal tumour, rosette-forming glioneuronal tumour of the fourth ventricle, papillary tumour of the pineal region, pituicytoma and spindle cell oncocytoma of the adenohypophysis. Histological variants were added if there was evidence of a diVerent age distribution, location, genetic proWle or clinical beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

113
9,965
13
433

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11,024 publications
(10,524 citation statements)
references
References 46 publications
113
9,965
13
433
Order By: Relevance
“…However, this finding leads to discuss the detection threshold of MB techniques. GG harbor a variable proportion of ganglion cells, from a few scattered cells to an authentic gangliocytoma (tumor composed entirely of ganglion cells with no glial tumor component) (Louis et al., 2007). The glial component is most often predominant in GG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this finding leads to discuss the detection threshold of MB techniques. GG harbor a variable proportion of ganglion cells, from a few scattered cells to an authentic gangliocytoma (tumor composed entirely of ganglion cells with no glial tumor component) (Louis et al., 2007). The glial component is most often predominant in GG.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors with the following histopathological diagnoses were selected: PA, pilomyxoid astrocytoma (PMA), ganglioglioma/gangliocytoma (GG/GC), anaplastic ganglioglioma (AGG), pleomorphic xanthoastrocytoma (PXA), anaplastic pleomorphic xanthoastrocytoma (APXA), dysembryoplastic neuroepithelial tumor (DNT), desmoplastic infantile ganglioglioma (DIG), astroblastoma (AB), and papillary glioneuronal tumor (PGNT). All cases were reviewed by two pathologists (one junior [QB] and one expert neuropathologist [AR]) and classified according to the 2016 WHO classification of tumors of the CNS (Louis et al., 2007). The entire cohort is described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gliomas are the most common type of primary tumors of the central nervous system and among them, GBM is the most common primary malignant brain tumor in adults and with the worst prognosis 21. Several clinical predictors of survival have been identified, such as age, preoperative functional status, and tumor extent 22.…”
Section: Discussionmentioning
confidence: 99%
“…The exact frequency of meningioma metastasizing to the pleura is unknown, but previous studies have reported the range to be from 5.5% 2 to 9.0% 4, suggesting that it is an extremely rare event. However, for WHO grade 3 meningioma 3, the rate of metastasis to other organs was as high as 42.8% 1, and only 4.3% to the pleura 2.…”
Section: Discussionmentioning
confidence: 92%